Wordpress basics for photographers. Part 1 - Concepcion, Rafael; Safari eBooks ([S.l. : KelbyTraining], 2010)
"Learn all the steps. From purchasing a domain name and web space, to installing Wordpress, creating pages and posts, to adding images. You will be amazed by how easy it is to setup your own photography blog! RC Concepcion takes you through from start to finish"--Resource description page (viewed April 29, 2010).
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title, presenter, and date from resource description page (viewed April 29, 2010).
Publisher from end credits.
Keywords: WordPress (Electronic resource); Photography -- Digital techniques; Electronic books